Climate Finance: Taking a Position on Climate Futures - Gareth Bryant; Sophie Webber (Agenda Publishing, 2024)
Climate change is increasingly contested on financial terms. Different actors are advancing competing climate visions and interests by adopting financial positions. International institutions urge action by identifying financing gaps needed to meet climate targets. The finance sector claims it holds the key to unlocking money needed for climate investment. Activists expose greenwashing while using financial tactics to undermine fossil fuels. Vulnerable countries demand wealthy governments repay historical climate debts.This book offers an accessible and critical guide to the political economy and economic geography of climate finance. It identifies six competing ""positions"" of climate finance to make sense of the array of financial instruments, institutions and ideas that are remaking the relationship between capitalism and climate change. Using a wide range of case studies, from green bonds, to divestment, carbon offsetting, climate tech, central banks, and international climate funds, the authors show how climate finance is shaping our collective climate futures.
Keywords: 320; Business & Economics; Development; Sustainable Development; Political Science; Public Policy; Economic Policy